Teachers’ Perception of HOTS-Based Learning in EFL Classroom - Giri , Putu Ayu Laras Pradnyani Nirmala (STKIP AGAMA HINDU SINGARAJA, 2021)
This study examines the perception of English teachers towards HOTS-based Learning in EFL classroom. This study was a survey study with interview as the data collection technique. The participants of the study were five English teachers in senior high school in Singaraja, Buleleng, Bali. The result of data analysis found that teachers’ awareness of implementing HOTS-based instruction starting from lesson plan, teaching strategies that promote higher thinking and assessment. However, teachers also faced difficulties in developing HOTS-based Instructions such as limited knowledge and lack of training. It is suggested that English teachers broaden their knowledge on developing HOTS-based instruction and conduct a discussion with peers and experts. The role of principle is also essential in giving instructions and training towards HOTS-based learning instructions.